Management of Complex Fractures: Modern Approaches, Patient Outcomes, and Evolving Strategies - Wojnowski, Antoni; Domińczak, Jan; Dobosz, Adam; Czarnecka, Sofia; Łuczyńska, Gabriela; Banatkiewicz, Joanna; Deka, Emilia; Bojanowska, Hanna; Babik, Karolina; Oliwia Bartkowska (Journal of Education, Health and Sport, 2026)
Introduction and Purpose: Complex fractures represent a significant challenge in orthopedic trauma, requiring sophisticated surgical techniques, multidisciplinary collaboration, and innovative fixation methods to optimize patient outcomes. This comprehensive review synthesizes current evidence on the management of complex fractures, focusing on modern surgical approaches, fixation innovations, patient outcomes, complications, and evolving treatment strategies. Description of the State of Knowledge: A narrative review was conducted across multiple databases, yielding 69 high-quality papers published primarily between 2020-2025, with selected seminal earlier studies included. Evidence was synthesized from systematic reviews, meta-analyses, randomized controlled trials, and prospective cohort studies addressing complex fracture management. Modern management emphasizes orthoplastic collaboration, minimally invasive techniques, and technological innovations including 3D printing, robotic-assisted surgery, and advanced imaging. Orthoplastic approaches demonstrate reduced infection rates (2.4-37%), with reported union rates ranging from >80% to near-complete union in selected series, and enhanced functional outcomes. Three-dimensional printing technology significantly reduces operative time, blood loss, and fluoroscopy use while improving anatomical reduction. Minimally invasive plate osteosynthesis achieves excellent functional outcomes in 65% of cases with rapid union rates. Complications remain a concern, with infection rates varying from 2.4% to 20% depending on fracture severity and management approach. Summary (Conclusions): Contemporary complex fracture management requires integrated multidisciplinary care, selective application of innovative technologies, and individualized treatment strategies. Future directions include artificial intelligence integration, personalized implant design, and enhanced biological augmentation strategies.